L’exposition préhistorique de la Galerie de l’Histoire du travail en 1867. Organisation, réception et impacts - Charlotte Quiblier (Les Cahiers de l'École du Louvre)
The Exposition Universelle of 1867, in addition to industrial exhibitors from around the world, presented a retrospective exhibition. Known by the name Galerie de l’Histoire du Travail, it featured works from before 1800. In the context of the strengthening of national identities and the debate about the age of humanity, several of the nations represented exhibited the earliest vestiges of the human occupation of their territory. Thus, the Galerie de l’Histoire du Travail was the setting for the first prehistoric exhibition. Organised by key figures in the nascent field of social science and linked to other major events in the structuring of this science, it played an important role in the construction and institutionalisation of prehistoric archaeology.